Pre-service teacher’s mathematical disposition through problem-solving and problem-posing based ignatian pedagogy - Yeni Fitriya; Ali Mustadi; Ikhlasul Ardi Nugroho; Andri Anugrahana (Jurnal Elemen, 2023)
Mathematical disposition is an important aspect that pre-service teachers must master to determine the success of mathematics learning. The objectives of this study were to show the statistical description and verify the research hypothesis regarding the comparison between problem-solving and problem-posing integrated with ignatian pedagogy as a novelty toward Elementary School Teacher Education students. Using a quantitative approach involving 84 students consisting of 9 males and 75 females as participants, used a comparison test between two learning models. The results of the parametric prerequisite test showed the value of Sig. <0.05 for normality and Sig. > 0.05 for homogeneity. However, data analysis can not be continued parametrically but was tested using Mann-Whitney U (non-parametric). The hypotheses test results concluded that H0 was accepted or there was no significant difference from the state of the students' mathematical disposition either using problem-solving or problem posing based on ignation pedagogy. It was evidenced by the probability value, which showed 0.221, which was > 0.05. The implications of this study directly recommend using appropriate learning models to improve the mathematical dispositions of pre-service teachers.